PENGARUH KUALITAS PELAYANAN DAN NILAI PELANGGAN TERHADAP LOYALITAS MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA GRACIA SKIN CLINIC SEMARANG - Eka Safitri Fajria; Naili Farida; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2013)
The purpose of this study is to determine the effect of service quality and value of customer loyalty through customer satisfaction as an intervening variable in Gracia Skin Clinic Semarang. The type of research is using explanatory research, the technique of collecting data through questionnaires. The sampling technique using purposive sampling and accidental sampling technique. The population was all patients of the Gracia Skin Clinic Semarang. While the sample of 100 respondents.The method of analysis used in this study is Part Analiyst or Path Analysis.Based on the descriptive analysis of 44% indicates that the variable quality of service  including both categories, 1% showed variable customer value category quite well, 21% indicated satisfaction variables including high enough category, and 23% showed loyalty variable category is quite high. Based on the calculations show that there is an influence of service quality, customer value variables, and variable customer satisfaction has positive and significant impact on the loyalty variable that is equal to 72,2%, while the remaining 27,8% is explained by other factors such as product quality, customer perception, promotion, brand image, and price. Based on the path analysis, the direct influence its value is greater than the indirect effect on the variables of service quality on loyalty. While the variable value customer loyalty, the indirect effect value is greater than the direct effect, up to variables of customer satisfaction to be intervening variables “amplifier” in relation to loyalty customer value variables.The Suggestions in this research is to improve the quality of service and hospitality to patients, pharmacies expand the space, creating an atmosphere of conducive to the consulting room, and repair procedures.